Baseline performance of high school rugby players on the Sport Concussion Assessment Tool 5 - Black, A. M.; Miutz, L. N.; Warriyar KV, V.; Schneider, K. J.; Yeate, K. O.; Emery, C. A. (Journal of Athletic Training, 2020)
Context: Version 5 of the Sport Concussion Assessment Tool (SCAT5) was released in 2017 with an additional 10-word list option in the memory section and additional instructions for completing the symptom scale.